Genetic Regulation of the Host-Fungus Interaction in the Pathogenesis of Aspergillosis - Antunes, Daniela (2019)
Purpose of Review There is significant interindividual variability in the development and progression of fungal diseases, most notably invasive pulmonary aspergillosis (IPA). The integration of individual traits into clinically valid procedures to predict the risk and progression of infection, and the efficacy of antifungal prophylaxis and therapy, will change the current healthcare landscape regarding the management of patients at risk of IPA and, likely, other fungal infections. Recent Findings Over the last decade, an expanding number of common polymorphisms associated with IPA have been reported, adding to the information available on monogenic defects underlying severe forms of the disease. Predisposition to IPA is therefore nowadays considered to result from a combination of clinical and host factors, with the latter being most likely regulated at the genetic level. Summary In this review, we address the contribution of the genetic profile of the host to the outcome of the host-fungus interaction and discuss the application of this information in potential strategies with the aim of moving towards personalized prognostics, diagnostics, and treatment.